Effect of Time and Waiting Facilities Toward The Satisfaction Level of Pregnant Women in Antenatal Care Services (Universitas Negeri Semarang, 2019)
Efforts to reduce mortality and morbidity in pregnant women by improving integrated ANC services which are comprehensive and integrated antenatal services, including promotive, preventive and curative and rehabilitative efforts. Community Health Centre is one of the basic health facilities that are used to carry out integrated ANC. Every pregnant woman is required to carry out an integrated ANC at the Community Health Centre in the first trimester. The purpose of this study was to analyze facilities and waiting times for the satisfaction level of pregnant women in ANC services. This research was a quantitative research, with a cross sectional approach. The sample of this study amounted to 109 samples with purposive sample technique. The instrument used a questionnaire. Data analysis was carried out by using two predictors regression. The results of F count are obtained that the F table is based ondk numerator = 2 and the denominator (109-2-1) = 106 for the error rate of 5% = 3.09 because F count is greater than F table, the correlation coefficient tested is significant. The most dominant factor obtained is the facility. The real contribution is 88.7% and the effective contribution is 5.23%, the waiting time has a relative contribution of 11.2% and the effective contribution is 0.66%. The conclusion is the influence between facilities and waiting time on the level of satisfaction of pregnant women in antenatal care services.